A Paradoxical Tumor-Suppressor Role for the Rac1 Exchange Factor Vav1 in T Cell Acute Lymphoblastic Leukemia - Robles Valero, Javier (2017)
Rho guanine exchange factors (GEFs), the enzymes that stimulate Rho GTPases, are deemed as potential therapeutic targets owing to their protumorigenic functions. However, the understanding of the spectrum of their pathobiological roles in tumors is still very limited. We report here that the GEF Vav1 unexpectedly possesses tumor-suppressor functions in immature T cells. This function entails the noncatalytic nucleation of complexes between the ubiquitin ligase Cbl-b and the intracellular domain of Notch1 (ICN1) that favors ICN1 ubiquitinylation and degradation. Ablation of Vav1 promotes ICN1 signaling and the development of T cell acute lymphoblastic leukemia (T-ALL). The downregulation of Vav1 is essential for the pathogenesis of human T-ALL of the TLX+ clinical subtype, further underscoring the suppressor role of this pathway. Robles-Valero et al. find that Vav1 facilitates binding of Cbl-b to the intracellular domain of Notch1 (ICN1) and promotes ICN1 degradation. Loss of Vav1 induces T cell acute lymphoblastic leukemia (T-ALL) by increasing ICN1 signaling, and TLX inhibits Vav1 expression to stimulate ICN1 signaling in TLX+ T-ALL.